Nitrous oxide and methane fluxes from urine and dung deposited on Kenyan pastures - Tully, Katherine L.; Abwanda, Sheila O.; Thiong'o, Margaret; Mutuo, Paul M.; Rosenstock, Todd S. (Wiley, 2017)
Livestock keeping is ubiquitous in tropical Africa. Urine and dung from livestock release greenhouse gases (GHGs), such as nitrous oxide (N2O) and methane (CH4), to the atmosphere. However, the extent of GHG’s impact is uncertain due to the lack of in situ measurements in the region. Here we measured N2O and CH4 emissions from cow urine and dung depositions in two Kenyan pastures that received different amounts of rainfall using static chambers across wet and dry seasons. Cumulative N2O emissions were greater under dung+urine and urine-only patches (P < 0.0001), more than three times higher in the wet compared with the dry season (P < 0.0001), and higher in the farm receiving higher rainfall overall (P < 0.0001). Cumulative CH4 emissions differed across treatments (P = 0.012), driven primarily by soil CH4 uptake from the urine-only treatment. Cumulative N2O emissions were positively related to N input rate in excreta. However, the relationship was linear during the dry season (r2 = 0.99; P = 0.001) and exponential during the wet season (r2 = 0.99; P < 0.0001). Nitrous oxide emission factors were 0.05% (dry season) and 0.18% (wet season) of N in urine and dung+urine, which is less than 10% of the IPCC Default Tier 1 emission factor of 2%. We predict that emissions from cattle urine in Kenya are approximately 1.7 Gg N2O–N yr−1 (FAO estimates 11.9 Gg N2O–N yr−1). Our findings suggest that current estimates may overestimate the contribution of excreta to national GHG emissions and that emission factors from urine and dung need to account for agroecosystems with distinct wet and dry seasons.